Sulfato‐β‐cyclodextrin induced multivalent supramolecular directional aggregation of cyanovinylene derivatives for achieving reversible near‐infrared fluorescence - Liu, Zhixue; Chen, Haiqi; Tian, Mengdi; Sun, Xinyao; Li, Yong‐Xue; Wu, Jie; Wang, Ruotong; Li, Bin; Li, Chunju; Liu, Yu (Aggregate (Hoboken), 2024)
Molecular aggregation or supramolecular aggregation‐induced emission is one of the research hotspots in chemistry, biology, and materials. Herein, we report negatively charged sulfato‐β‐cyclodextrin (SCD) induced cyanovinylene derivatives (DPy‐6C) directional aggregation to form regular nanorods (DPy‐6C@SCD) through supramolecular multivalent interactions, not only achieves ultraviolet‐visible absorption redshifted from 453 to 521 nm but also displays near‐infrared (NIR) aggregation‐induced emission with a large spectral redshift of 135 nm. The DPy‐6C monomer presents random nanosheets with weak fluorescence but obtains regular aggregates after assembly with SCD through electrostatic interactions. In the presence of H+, the DPy‐6C@SCD can further aggregate into elliptical nanosheets without fluorescence changes due to the protonation of secondary amines. In contrast, the morphology of DPy‐6C@SCD becomes flexible and sticks together upon the addition of OH− with an emission blue shift of 72 nm and a 90‐fold intensity increase because of disrupting the stacking mode of aggregates, thereby achieving acid‐base regulated reversible fluorescence behaviors that cannot be realized by DPy‐6C monomer. The DPy‐6C@SCD can efficiently select the detection of volatile organic amines both in liquid and gas phases within 5 s at the nanomolar level. Taking advantage of RGB analysis and calculation formula application, the DPy‐6C@SCD has been successfully used to monitor various organic amines on a smartphone, accompanied by naked‐eye visible photoluminescence. Therefore, the present research provides an efficient directional aggregation method through supramolecular multivalent interactions, which not only realizes topological morphology transformation but also achieves reversible NIR luminescent molecular switch and high sensitivity organic amines fluorescent sensing devices. Sulfato‐β‐cyclodextrin can induce the directional aggregation of cyanovinylene derivatives (DPy‐6C) to form near‐infrared aggregates, displaying topological morphology changed from random nanosheets to regular nanorods with an emission spectrum redshift of 135 nm. The aggregates exhibit acid‐base‐regulated reversible fluorescence behaviors, which cannot be realized by DPy‐6C and can be used for monitoring volatile organic amines on a smartphone.